Analysis of apple chips business development strategies using business model canvas approach and SOAR-AHP method - Mustaniroh, Siti Asmaul; Putri, Salma Rana; Maligan, Jaya Mahar (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
The study focuses on SMEs X, a producer of various processed fruit products, primarily apple chips. The business experienced a 90% decline in revenue due to an 8-month market closure during the Covid-19 pandemic, with ongoing challenges such as reduced revenue and production capacity post-pandemic. This study aims to identify business models in SMEs using the Business Model Canvas (BMC) approach, develop alternative business strategies through SOAR analysis of BMC elements, prioritize these strategies using the Analytical Hierarchy Process (AHP) method, and enhance their BMC. Four expert respondents participated in the study. The research results highlight the current business conditions across the 9 BMC elements. The SOAR matrix produced eight alternative strategies, prioritized using the AHP method, including optimal production planning and scheduling (OR2), strengthening apple chips brand awareness (OA2), disseminating freeze-drying production technology innovations (OA1), developing business unit production (SA2), expanding the marketplace (SA1), maximizing the use of social media (OR1), product quality standardization (SR1), and forming partnerships with other fruit chip SMEs to innovate freeze-dried products (SR2). The BMC was further developed by integrating SR2 and OA1 into the key partnerships element, SA2 into the key resources element, OA2, OR1, and OA2 into the key activities element, SR1 into the value proposition element, and SA1 into the channel element.